2012
DOI: 10.1038/emboj.2011.488
|View full text |Cite
|
Sign up to set email alerts
|

Raising cytosolic Clin cerebellar granule cells affects their excitability and vestibulo-ocular learning

Abstract: Cerebellar cortical throughput involved in motor control comprises granule cells (GCs) and Purkinje cells (PCs), both of which receive inhibitory GABAergic input from interneurons. The GABAergic input to PCs is essential for learning and consolidation of the vestibulo‐ocular reflex, but the role of GC excitability remains unclear. We now disrupted the Kcc2 K‐Cl cotransporter specifically in either cell type to manipulate their excitability and inhibition by GABAA‐receptor Cl− channels. Although Kcc2 may have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 67 publications
9
112
0
Order By: Relevance
“…45 and for review In particular, the deficits observed in AS mice are strikingly similar to those identified in a recently reported mouse mutant with a granule cell-specific mutation in the KCC2 KCl cotransporter gene; this genetic manipulation depolarizes granule cells by increasing their cytosolic chloride concentration. Like AS mice, these mutants also show severely impaired phase-reversal learning, while their OKR, VOR, and VVOR basic motor performance and gain-decrease learning are unaffected (38). Together, these findings suggest that defective Golgi cell functioning might contribute to the observed cerebellar phase-reversal learning deficits in AS mice.…”
Section: Discussionmentioning
confidence: 78%
“…45 and for review In particular, the deficits observed in AS mice are strikingly similar to those identified in a recently reported mouse mutant with a granule cell-specific mutation in the KCC2 KCl cotransporter gene; this genetic manipulation depolarizes granule cells by increasing their cytosolic chloride concentration. Like AS mice, these mutants also show severely impaired phase-reversal learning, while their OKR, VOR, and VVOR basic motor performance and gain-decrease learning are unaffected (38). Together, these findings suggest that defective Golgi cell functioning might contribute to the observed cerebellar phase-reversal learning deficits in AS mice.…”
Section: Discussionmentioning
confidence: 78%
“…In other neurons, such as neocortical pyramidal cells, where GABA has been shown to depolarize axons, it is unclear whether NKCC1 is expressed in adults; however, KCC2 protein is excluded from the axonal compartments (Szabadics et al 2006). In the adult cerebellar cortex, both KCC2 and NKCC1 mRNA are present in granule cells (Mikawa et al 2002), and KCC2 protein appears to be completely absent in PFs (Seja et al 2012). Thus, either the presence of NKCC1 or the absence of KCC2 from PFs likely accounts for the compartmental differences in chloride reversal potential.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the simultaneous presence of KCC-mediated Cl − extrusion and GABA A receptor (GABA A R)-mediated Cl − influx, a dynamic steady state will be established in which changes in Cl − conductance or KCC activity will be reflected in [Cl − ] i . This classical pump–leak relationship 273 is made use of in experiments addressing the transport capacity of KCC2 and NKCC1 by experimentally inducing an exogenous excess or deficit of Cl − , respectively, in a neuron 5,146,185,274,275 .…”
Section: Expression Of Cccs In the Cnsmentioning
confidence: 99%
“…1a). Nevertheless, the physiological roles of KCC3 in neurons remain largely unknown 5,6,51,116,117 (TABLE 1). The idea that KCC3 has important roles in the healthy nervous system is strongly supported by the fact that peripheral neuropathy associated with agenesis of the corpus callosum (ACCPN; also known as Andermann syndrome) is caused by genetic impairment of KCC3 (REFS 46,116,118).…”
Section: Expression Of Cccs In the Cnsmentioning
confidence: 99%